Perbedaan Hasil Pemeriksaan Sianida Urine dengan Variasi Waktu Penundaan Kadar Awal (1, 2, 4, 8, 24 Jam) yang Disimpan Pada Suhu Ruang dan Rentang Suhu 2-8°C - Susi, Ni Nengah; Sudarma, Nyoman; Abadi, Fairuz (Jurnal Kesehatan Rajawali, 2025)
This study aims to determine the differences in the results of cyanide levels in urine stored at room temperature (25°C) and cold temperatures (2–8°C) with variations in the initial delay time (1, 2, 4, 8, and 24 hours). Urine samples that have been added with standard KCN solution were analyzed using a colorimetric test kit. Data were tested using a two-way ANOVA method using Aligned Rank Transformation (ART) followed by post-hoc tests (emmeans and contrast). The results showed that temperature and time factors had a significant effect individually on cyanide levels (p <0.001), but there was no significant interaction between the two (p <0.017511) this value is greater than 0.01 so it can be concluded that there is no significant effect of the interaction between temperature and time on cyanide levels. The highest cyanide levels were recorded at the initial level of 0.0400 ppm and decreased significantly over time to 0.0167 ppm at room temperature. and at cold temperatures it is more capable of maintaining cyanide levels to 0.0267 ppm. Storage at cold temperatures is more capable of maintaining cyanide levels compared to room temperature. These results indicate the importance of temperature management and storage time in maintaining the validity of cyanide examination results in urine.